A role of diagnostic imaging in early breast cancer diagnosis - Bianek-Bodzak, Agnieszka; Studniarek, Michał (Contemporary Oncology/Współczesna Onkologia, 2002)
In the light of epidemiological data the role of early breast cancer diagnosis is discussed. Succesful treatment depends on stage of the tumor, thus many studies are conducted in order to find a good diagnostic method in preclinical stage and to elaborate a new diagnostic criteria for the most popular ones. Carcinoma ductale in situ is diagnosed in 20% of clinicaly asymptomatic cases. About 60% of them present very subtle or even indirect mammographic signs, thus additional projections, magnified images and multiple biopsies are needed to confirm the diagnosis. Despite the high sensitivity, reaching in some studies 92%, there are still 8-25% of false negative results. Variable anatomic structure of normal breast is an additional hard circumstance in the mater. Neverthless conventional mammography (film mammography) applied with ultrasonography and FNAB is still the best method in early breast cancer diagnosis. Digital mammography, a method of potentialy great diagnostic possibilities, is now under investigation. There are some big comparative multicenter trials being now performed in United States. Mammoscintigraphy, magnetic resonance mammography and FDG-PET are well known methods when some diagnostic problems are to be solved. Malignant breast tumours present strong enhancement immediately after i.v. injection of Gd-DTPA and quite fast diminution of contrast medium concentration. Benign tumours are characterized by the different time-concentration curve (with a long plateau), thus on this basis it is possible to differentiate ones from anothers. The sensitivity of the method is claimed to be as high as 96-99%. The same phenomenon is the base of mammoscintigraphic findings. In this case however the high specificity is proved, so mammoscintigraphy enables to exclude a presence of breast cancer with a very high probability. In the cases with "lumpy" breast it is the resonable method to relive the women from fear and unnecessairy invasive diagnostics. Limphoscintigraphy plays the substantial role in localization of sentinel lymph node and in the choice of treatment strategy. It is applied as a conventional planar or SPECT scintigraphy, but also as an intraoperative procedure. In the breast cancer staging the most promissive method seems to be FDG-PET, as it enables not only very accurate diagnosis of primary neoplasmatic focus but lymph nodes involvement and distant metastases as well. The malignant tumours cummulate F18-fluoro-deoxy-glucose in not clear way, but it is proved that both sensitivity and specificity of the method are very high. In the last years some instalations dedicated to real functional/anatomical image fusions were developed, i.e. PET/CT scanners, thus now it is posssible not only to find hyperactive malignant focus, but to place it in the background of surrounding tissues as well.